Multidetector computed tomography has replaced conventional intravenous excretory urography in imaging of the kidneys: A scoping review of multidetector computed tomography findings in renal tuberculosis - Ntombizakhona B.A. Mthalane (South African Journal of Radiology, 2018)
Background: Tuberculosis (TB) is a worldwide infectious disease burden, especially in non-developed countries, with increased morbidity and mortality among human immunodeficiency virus (HIV)-infected patients. Extrapulmonary TB is rare and renal TB is one of the commonest manifestations. The end result of renal TB is end-stage renal disease; however, this can be avoided if the diagnosis is made early. The diagnosis of renal TB is challenging because of the non-specific presentation and low sensitivity of clinical tests. Although the sequel of TB infection in the kidney causes varying manifestations depending on the stage of the disease, multidetector computed tomography (MDCT) is capable of demonstrating early findings. We performed a 20-year scoping review of MDCT findings in renal TB to promote awareness.